Pois para que (ainda) servem os poetas em tempos de indigência? Poetas em tempos de indigência - Moreira, Jacqueline (2024)
Triggered by the question ‘how does one read on the eve of the end of the world?’ We firstly opted to establish a definition frame on the concept of the end of the world. We chose to always reflect upon the theme assuming the constant motion between the singular and the collective aspects. The poetic prose posed itself as a means of conveying the end-of-the-world experience. We hereby restate not only the factual existence of poetry, but also its existential need in destitute times. In order to support such statement, we resort to some philosophical and psychoanalytic considerations and illustrate them with some examples of poems, namely Autotomy by Wisława, Sou Negro by Solano Trindade, Lazeado by André Capilé, and A Porca by Adelaide Ivánova.